Social Media Paradox: An Exploration on the Bright and Dark Sides of Social Media - Louie Giray (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2021)
This paper explores a discourse about the bright and dark sides of social media, which is rooted from various studies. It offers also a reflection about the topic. The paper uses literature review as a research methodology to make sense of the data gathered. In conclusion, social media is not beneficial nor malevolent; it is neither neutral. It is only a medium of whatever one wants to convey. Therefore, the bright and dark sides of social media can be traced upon on how a specific individual uses the platform. It just becomes beneficial or untoward depending on the users themselves. Factors, such as, but not limited to, intention, caution, usage, and self-control, contribute to outcomepositive or negative in nature.